Attracting private investment in public-private-partnership: tax reduction or risk sharing - Wang, Bing; Geng, Linna; Moehler, Robert; Tam, Vivian W. Y. (Journal of Civil Engineering and Management, 2024)
With the financial burden of government increasing, the Public-Private-Partnership (PPP) model has become an alternative method to develop public infrastructure. To efficiently promote the private sector to participate in PPP, making a proper incentive policy is critical for the government. This paper examined the effects of two governmental support policies, i.e., tax reduction and risk-sharing, on the investment decision of the private sector, and further compared the relative efficacy of these two policies. The results manifest that: first, both tax reduction and risk-sharing policies motivate private sector to invest earlier; second, although the capital structure decision of the private sector is free from the influence of the risk-sharing policy, the optimal debt level under tax reduction policy shows a U-shape relationship with the incentive ratio; third, when completion risk is large, there exists efficiency loss for total benefits of the project under the risk-sharing incentive policy. Besides, the efficacy of two incentive policies varies depending on the scenario. Firstly, given the same incentive ratio, the risk-sharing policy proves to be more effective than the tax reduction policy. Secondly, when considering the same level of incentive loss for government, tax reduction policy outperforms than risk-sharing policy in terms of efficacy. Thirdly, the efficacy of these policies also depends on the completion risk level: under small completion risk, risk-sharing policy is more effective, whereas under large completion risk, the tax reduction policy takes precedence. Based on these findings, some managerial insights that could assist government in formulating more effective incentive policies are proposed.